Analisis Model Jaringan Vehicular Ad Hoc Network Dengan Transmisi Tworayground Pada Topologi Optimized Link State Routing - Mirsha Akbar; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The Vehicular Ad hoc network itself is an infrastructure which has the function to communicate with each other between vehicles and occurs through wireless links found on each node. To implement the Optimized Link State Routing protocol which is proactive and periodically sends a control message that has the goal of maintaining the destination path so that it is always available or stand by if needed. The TwoRayGround transmission performance will be performed in a comparison that matches the test parameters such as Packet Delivery Ratio, Throughput, and Delay. Therefore, from this problem a solution can be taken which uses OLSR protocol and TwoRayGround transmission in the VANET scope to make it more efficient and effective for sending a vehicle node. From the results of tests that have been carried out, Packet Delivery Ratio, Throughput, and Delay, in scenario which is the density of a node obtained from the OLSR protocol has a value in the packet delivery ratio of 7.2131%, a value at 0.84 kbps throughput, and a value at a delay of 0.41729 ms high. Referes to the test results of the three parameters that the OLSR protocols can be used on VANET.